2018
DOI: 10.1007/s11103-018-0699-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen activated protein kinase 6 and MAP kinase phosphatase 1 are involved in the response of Arabidopsis roots to l-glutamate

Abstract: The function and components of L-glutamate signaling pathways in plants have just begun to be elucidated. Here, using a combination of genetic and biochemical strategies, we demonstrated that a MAPK module is involved in the control of root developmental responses to this amino acid. Root system architecture plays an essential role in plant adaptation to biotic and abiotic factors via adjusting signal transduction and gene expression. L-Glutamate (L-Glu), an amino acid with neurotransmitter functions in animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Chinensis L.) [75]. Isolated AAs, including leucine (L-Leu), lysine (L-Lys), tryptophan (L-Trp), and glutamate (L-Glu), repress cell division and elongation in Arabidopsis primary roots [76], and its effect could be associated with auxin-and mitogen-activated protein kinase (MAPK) signaling [76,77]. All these findings indicate that PHs can improve the root system architecture, and future investigations will be performed to decipher regulatory molecular networks and understand cross-talks between hormones and peptides in PH-controlled root physiology.…”
Section: Root Architecturementioning
confidence: 99%
“…Chinensis L.) [75]. Isolated AAs, including leucine (L-Leu), lysine (L-Lys), tryptophan (L-Trp), and glutamate (L-Glu), repress cell division and elongation in Arabidopsis primary roots [76], and its effect could be associated with auxin-and mitogen-activated protein kinase (MAPK) signaling [76,77]. All these findings indicate that PHs can improve the root system architecture, and future investigations will be performed to decipher regulatory molecular networks and understand cross-talks between hormones and peptides in PH-controlled root physiology.…”
Section: Root Architecturementioning
confidence: 99%
“…Nitrate, acting as a signal at the root tip, abolishes the glutamate primary root inhibition effect ( Walch-Liu and Forde, 2008 ). At least two mitogen-activated protein kinase (MAPK) pathways were implicated in this process ( Forde et al, 2013 ; López-Bucio et al, 2018 ). It was also suggested that auxin is acting downstream of glutamate ( Walch-Liu et al, 2006 ), and it might be the case that auxin acts downstream from one of these MAPK pathways.…”
Section: Glutamatementioning
confidence: 99%
“…Given the fact that Tyr phosphorylation of MPKs is required for their activation [ 89 , 90 ], these studies support a potential role of Tyr phosphorylation in modulating the auxin signaling. A recent study also implicated MPK6 and MAP Kinase Phosphatase 1 (MKP1), a known DUSP that could dephosphorylate pSer/pThr/pTyr residues [ 91 ], in a growth response of Arabidopsis roots to L-Glutamate by regulating auxin distribution and response [ 92 ]. A recent chemical biology study has demonstrated a role of the auxin-induced phosphorylation at Tyr248 residue ( Figure 2 and Table 1 ) of an Arabidopsis Receptor for Activated C Kinase 1 (RACK1, a WD-40 type scaffold protein) in the auxin-mediated lateral root development [ 65 ].…”
Section: The Role Of Tyr Phosphorylation In Plant Growth Developmentmentioning
confidence: 99%